Faktor-Faktor yang Berpengaruh terhadap Perpindahan Kerja Karyawan (Studi Kasus terhadap Rumah Sakit di Batam) - Nerissa Arviana; Evi Silvana Muchsinati (Universitas Kristen Maranatha, 2016)
This research aims to analyze factor that affects employee turnover on hospital in Batam. Sample is being collected from hospital in Batam by using the purposive sampling method. Public hospital is being choosed as sampling place.Questionaires distributed were 200 questionaires and 159 of them were being collected. Total data used in the analysis is 111 questionaire because 48 of the collected questionaire do not fulfill the sampling criteria. Partial Least Square ischosen as the statistical method. Independent variables in this research are compensation, job security, working condition, organizational justice, co-worker support, supervisor support, work-life balance, promotion opportunities, researchand development, and organization commitment. Employee turnover is the only dependent variable in this research. Research results show that job security, workingcondition, and work-life balance have significant influence toward employee turnover. Compensation, organizational justice, co-worker support, supervisor support, promotion opportunities, research and development, and organizationalcommitment show nosignificant influence.Keywords: Turnover, Job security, Working condition,Co-worker support, Work life balance, Promotion opportunity